« Gender Equality and Economic Inequality: Impact on Marriage » dans Gender and couple relationships - Coontz, Stephanie (Gender and couple relationships, 2016)
Changes in aggregate marriage rates and in the internal dynamics of individual marriages should be understood as the outcome of two powerful but very different trends in gender and class relations. One trend is the uneven but undeniably dramatic progress toward equality in personal life and cultural values, which has led to widespread repudiation of centuries-old gender hierarchies. The other trend is an equally powerful movement toward growing inequality, insecurity, and unpredictability in economic life, which has resulted in substantial losses for the most historically vulnerable and least-educated sections of the workforce. The ongoing gender revolution interacts with widening economic inequality in complex ways, increasing the benefits of marriage for individuals with higher earning power while increasing the risks of marriage for low-income individuals, especially women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; care; cours; discipline; discours dominant; droits des femmes*; famille; inégalités; mariage; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; soc2262; sociologie; systèmes d'oppressions; thématiques; états-unis

Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social

Sur le terrain de l’émotion : déconstruire la question émotionnelle en géographie pour reconstruire son horizon épistémologique - Volvey, Anne (Carnets de géographes, 2016)
Ce texte interroge la part esthétique de la création géographique et présente des corpus et des outils théoriques et conceptuels pour travailler cette question d’épistémologie disciplinaire. Dans une première partie, il s’attache à une généalogie de l’évolution de la prise en compte du phénomène de l’émotion dans la recherche – de problème en fait significatif, puis en moyen de la connaissance géographique – à travers les réflexions conduites, notamment par la géographie féministe et qualitative anglophone, sur la méthodologie disciplinaire du terrain. Sur ce fondement, il présente les trois régimes esthétiques de savoir spatial attachés aux standards méthodologiques successivement adoptés par la discipline – régimes scopique du terrain masculiniste, linguistique et haptique du terrain féministe et qualitatif. Dans une seconde partie critique, en revenant sur le modèle du care privilégié par les géographies féministes et qualitatives pour reconstruire la politique de la méthode sur des bases relationnelles (ou intersubjectives), il traite des limites politiques rencontrées par ces géographies pour fonder pleinement un autre régime de scientificité disciplinaire à partir de l’émotion. A contrario, il montre comment la psychanalyse du care (ou psychanalyse transitionnelle) prise au sérieux, non seulement pour ses trouvailles méthodologiques et conceptuelles mais pour sa théorie relationnelle de l’identité-subjective, peut devenir l’outil d’élaboration d’une épistémologie qualitative basée sur l’émotion.
https://journals-openedition-org.proxy.bibliotheques.uqam.ca/cdg/541
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; care; corps; discipline; géographie; psychanalyse; périodes historiques; ressource en ligne; sciences; sciences humaines; thématiques; émotions; épistémologie; étude qualitative